2020
DOI: 10.3390/polym12071509
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylidene Fluoride-Graphene Oxide Membranes for Dye Removal under Visible Light Irradiation

Abstract: In this study, polyvinylidene fluoride (PVDF)-graphene oxide (GO) membranes were obtained by employing triethyl phosphate (TEP) as a solvent. GO nanosheets were prepared and characterized in terms of scanning and transmission electron microscopy (SEM and TEM, respectively), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), chemical analysis and inductively coupled plasma mass spectroscopy (ICP). Two different phase inversion techniques, Non-Solvent Induced Phase Separation (NIPS) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…It can be observed that the contact angle slightly decreases as the pure polymer hosts more EOGO nanoplatelets up to 0.5 wt% while it rises again at 1 wt% loading. It can be supposed that at lower EOGO contents, the presence of hydrophilic oxygen functional groups contributed to modification of the surface nature leading to moderately lower hydrophobicity of the polymer as revealing lower contact angles, 92 although this effect subsequently became poor as higher amounts of EOGO were introduced in the matrix; in a way that, this higher EOGO content affects the homogeneous distribution of the nanoplatelets in the matrix (Figure S3) leaving them to intertwining as well as overlapping or confinement, so that finally fewer hydrophilic groups are available at the surface 93,94 . Besides, another reason for such a multistage behavior may be the changes in surface roughness obtained by AFM as mentioned earlier in section 3.1.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that the contact angle slightly decreases as the pure polymer hosts more EOGO nanoplatelets up to 0.5 wt% while it rises again at 1 wt% loading. It can be supposed that at lower EOGO contents, the presence of hydrophilic oxygen functional groups contributed to modification of the surface nature leading to moderately lower hydrophobicity of the polymer as revealing lower contact angles, 92 although this effect subsequently became poor as higher amounts of EOGO were introduced in the matrix; in a way that, this higher EOGO content affects the homogeneous distribution of the nanoplatelets in the matrix (Figure S3) leaving them to intertwining as well as overlapping or confinement, so that finally fewer hydrophilic groups are available at the surface 93,94 . Besides, another reason for such a multistage behavior may be the changes in surface roughness obtained by AFM as mentioned earlier in section 3.1.…”
Section: Resultsmentioning
confidence: 99%
“…The use of hybrid systems integrating physical and chemical treatments is frequent for colour removal as a strategy to reduce contamination. Photocatalysts combined with membrane systems allowed Methylene Blue (MB) degradation, with 83.3% removal in 370 min; achieved by controlling pH and salt concentration [149]. Photocatalytic degradation systems under visible light have employed to evaluate the degradation of Reactive Violet 5 (RV5), and 50Fe-TiO 2 level achieved higher degradation efficiency (47.6%) in 9 h [155].…”
Section: Treatment Of Coloured Wastewatermentioning
confidence: 99%
“…In addition, their abatement represents a relevant problem in the wastewater treatment processes because generally they are very stable toxic compounds. For this purpose, photocatalytic membrane reactors can be interesting technologies employed for chemical conversion of organic dyes into safe (nontoxic) or harmless compounds with minimum consumption of energy and reagents [ 24 , 27 , 36 , 37 ].…”
Section: Hmps Obtained By Coupling Membrane Processes With Photocamentioning
confidence: 99%
“…Various types of membranes have been studied to be applied in photocatalysis, such as inorganic and polymeric, under UV and visible light irradiations [ 24 , 27 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Moreover, the use of visible light in photocatalysis permits the use of renewable solar energy in view to obtain a sustainable process [ 24 , 27 ].…”
Section: Hmps Obtained By Coupling Membrane Processes With Photocamentioning
confidence: 99%
See 1 more Smart Citation